Analisis Penerapan Assesment For Learning Dalam Pembelajaran Matematika di SMP - Danial, Danial; Kalfin, Kalfin; Rais, Damar (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
This study was motivated by the importance of implementing Assessment for Learning in mathematics instruction to support continuous monitoring of students’ learning progress, the provision of feedback, and the improvement of the learning process. The study aimed to analyze the implementation of Assessment for Learning in mathematics learning at SMP Negeri 5 Sinjai, particularly in the aspects of formative assessment, remedial teaching, feedback, and the follow-up use of assessment results in instructional planning. This study employed a qualitative approach with a descriptive research design. The research subjects were a mathematics teacher eighth-grade, while the data were collected through classroom observations and interviews. The data were analyzed using descriptive qualitative analysis through the stages of data reduction, data display, and conclusion drawing. The findings revealed that the teacher had implemented formative assessment in the form of quizzes, assignments, and daily assessments, which were adjusted to students’ characteristics and the cognitive level of the material. When the learning objectives were not achieved, the teacher conducted remedial teaching through reteaching, grouping students, and adjusting the level of difficulty of the assessment items. Feedback was provided in the form of scores and verbal responses, and its effectiveness was monitored through subsequent assessments. Assessment results were also used to improve teaching modules, assessment instruments, and instructional strategies. These findings indicate that Assessment for Learning plays an important role in creating mathematics instruction that is adaptive, reflective, and oriented toward students’ needs.